Optimizing Digital Entrepreneurship Interest Among University Students: The Impact of SEHATI Program and Halal Certification in The Age of Social Media - Suganda, Asep Dadan; Nawawi, Ma'mun; Suraya, Ismi (Journal of Islamic Economics and Finance Studies, 2024)
The university is committed to developing digital entrepreneurship among students, which is realized through concrete efforts in the classroom by integrating entrepreneurial and Sharia business learning and e-commerce and outside the classroom with digital marketing training programs for students. Despite having interest and potential in digital entrepreneurship, students may face limited access and knowledge related to the halal certification process. The SEHATI program, which offers free halal certification, can be a solution to overcome these barriers. However, the effectiveness of this program in increasing students' interest in digital entrepreneurship still needs to be investigated. This research was conducted to determine the influence of the free halal certification program (SEHATI) and social media on students' interest in digital entrepreneurship. This study uses descriptive analysis with a quantitative approach. Data collection is based on surveys and other relevant sources measuring digital entrepreneurial interest, participation in the halal certification program, and the level of social media use. Then, the multiple linear regression model is used with Significance Tests using T-test and F-test. The research results show that the SEHATI program and social media significantly influence students' interest in digital entrepreneurship both partially and simultaneously